2014
DOI: 10.3748/wjg.v20.i25.8268
|View full text |Cite
|
Sign up to set email alerts
|

Proximal gastrectomy with jejunal interposition and TGRY anastomosis for proximal gastric cancer

Abstract: PGJI is a safe, radical surgical method for proximal gastric cancer and leads to better outcomes in terms of the single-meal food intake and hemoglobin level, compared with TGRY in the short term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 0 publications
1
21
0
1
Order By: Relevance
“…This study also found that hemoglobin levels in the LAPG group were significantly higher 2 years after surgery, in agreement with previous reports [25][26][27]. LAPG results in the maintenance of Castle intrinsic factor and the duodenal passage of food, which is very important for the absorption of dietary iron [28].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This study also found that hemoglobin levels in the LAPG group were significantly higher 2 years after surgery, in agreement with previous reports [25][26][27]. LAPG results in the maintenance of Castle intrinsic factor and the duodenal passage of food, which is very important for the absorption of dietary iron [28].…”
Section: Discussionsupporting
confidence: 82%
“…In Korea, Ahn et al [24] concluded that LAPG with double-tract reconstruction is a feasible and acceptable method for treating proximal early gastric cancer. In China, Zhao et al [25] concluded that proximal gastrectomy with jejunal interposition is a safe, radical surgical method for proximal gastric cancer. Gastroesophageal acid reflux seldom occurs after proximal gastrectomy with jejunal interposition or double-tract reconstruction, so that routine acid control such as PPI administration is not required.…”
Section: Discussionmentioning
confidence: 99%
“…EJ after PG is similar to Roux-en-Y EJ after TG in terms of anastomosis-related late complications (0~10.2% vs 1.8~8.7%). 18,[29][30][31] Although abdominal fullness, discomfort rumbling, and hiccups are more frequently found after EJ in PG due to the disturbance of food passage by the interposed bowel. 9…”
Section: Discussionmentioning
confidence: 99%
“…The 13th edition of Guidelines for the Treatment of Gastric Cancer in Japan has classified numbers 5, 6, 12a, 12b, and 14v lymph nodes into the D3 lymph nodes of AEG [11]. Therefore, it was feasible to perform limited proximal gastrectomy D1+ surgery toward AEGII/III GC patients [12, 13]. …”
Section: Discussionmentioning
confidence: 99%